ANALISIS PENGUKURAN KINERJA RUMAH SAKIT DENGAN PENDEKATAN BALANCED SCORECARD (Studi Kasus Pada RSI Hasanah Muhammadiyah Mojokerto) - Permatasari, Nanda Octavia Fitri (Jurnal Ilmiah Mahasiswa FEB, 2017)
The aim of this research is to measure performance of Rumah Sakit Islam (Islamic Hospital) Hasanah Muhammadiyah Mojokerto through Balanced Scorecard. The measurement is divided into four perspectives : financial, learning and growth, internal business process, and customer perspective. This primary and secondary data of this research are derived from 2013 up to 2015. The results of the study show that RSI Hasanah Muhammadiyah Mojokerto in general has performed well. The financial perspective analysis shows a good results as indicated by the increase of efficiency and ROI. However, in terms of the learning and growth, internal business process, and customer perspective, the Hospital is considered as performing adequately and thus needs some improvements in some aspects, especially employee turnover, BOR, ALOS, TOI, complain level, and customer retention.Keywords: Performance Measurements, Balanced Scorecard, Hospital